The Vocational High School Students' Perceptions of Collaborative Learning in Reading - Effendi, Try Suheri; Wijirahayu, Suciana (Jetlal, 2024)
This research explores vocational high school students' perceptions regarding the application of collaborative learning in the context of reading recount and biographical texts. This research uses quantitative descriptive methods to measure and analyze attitudes, experiences and results related to collaborative learning techniques among students. Data was collected through a structured questionnaire distributed to vocational school students. Findings indicated that students generally had positive perceptions of cooperative learning, highlighting its increased understanding and engagement with retelling and biographical texts. Additionally, the results show collaborative learning fosters a supportive learning environment that encourages student participation and interaction. These insights are invaluable for educators who wish to implement cooperative learning strategies to improve reading skills in vocational education settings.